2021
DOI: 10.21106/ijma.524
|View full text |Cite
|
Sign up to set email alerts
|

Geographic, Health Care Access, Racial Discrimination, and Socioeconomic Determinants of Maternal Mortality in Georgia, United States

Abstract: Over the past decade, the United States has been taking steps to reduce its rising maternal mortality rate. However, these steps have yet to produce positive results in the state of Georgia, which tops the list of all 50 states with the highest maternal mortality rate of 46.2 maternal deaths per 100,000 live births for all women, and a maternal mortality rate of 66.6 deaths per 100,000 live births for African American women. In Georgia, several social determinants of health such as the physical environment, ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…To prevent and reduce these maternal deaths, numerous interventions have been developed. One of such interventions is the UN’s adoption of Sustainable Development Goals (SDGs)—the target of one of the SDG-3 is reducing the global maternal deaths to less than 70 deaths per 100,000 livebirths by 2030 [ 6 , 7 ]. Also, in 2021, five new targets were established to help countries get back on track in decreasing maternal deaths and tracking progress against the SDGs.…”
Section: Introductionmentioning
confidence: 99%
“…To prevent and reduce these maternal deaths, numerous interventions have been developed. One of such interventions is the UN’s adoption of Sustainable Development Goals (SDGs)—the target of one of the SDG-3 is reducing the global maternal deaths to less than 70 deaths per 100,000 livebirths by 2030 [ 6 , 7 ]. Also, in 2021, five new targets were established to help countries get back on track in decreasing maternal deaths and tracking progress against the SDGs.…”
Section: Introductionmentioning
confidence: 99%
“…Moving beyond mere identi cation as risk factors for maternal deaths (15,41,43,47), we observed that structural determinants such as poverty, low educational status, and elementary occupation levels had forced families towards social isolation, creating a synergistic effect to obtain minimal or no support from society. However, this study did not re ect any discrimination due to cast, ethnicity, racism, culture, or religion-related to maternal deaths as reported elsewhere in the world (15,41,44,(47)(48)(49), indicating the cultural harmony and culturally equitable health services existing in Sri Lanka.…”
Section: Discussionmentioning
confidence: 96%
“…Moving beyond mere identification as risk factors for maternal deaths [ 48 ], we observed that structural determinants such as poverty, low educational status, and elementary occupation levels had forced families towards social isolation, creating a synergistic effect to obtain minimal or no support from society. However, this study did not reflect any discrimination due to cast, ethnicity, racism, culture, or religion-related to maternal deaths as reported elsewhere in the world [ 49 ].…”
Section: Discussionmentioning
confidence: 96%